Fragments of Lost Origins - Pekka Tuominen (Suomen Antropologi)
The cityscape of contemporary Istanbul consists of intricate boundaries that play a significant role in the everyday lives of its inhabitants. This research report explores how various historical narratives of Turkishness are related to spatial divisions of the city and different frameworks of belonging and argues that a notion of an authentic self has become crucial in defining urbanity in Istanbul. In contesting historical understandings, the ancestral Central Asian Turkic civilizations, the imperial history of the Ottoman Sultans, and the birth of the Turkish Republic are seen as a series of ruptures with complex definitions of authenticity and foreignness, especially in relation to religion and ethnicity. The aim of the study is to show how different historically constructed frameworks of appropriate practices and norms are associated with urban egalitarian spaces and traditional neighbourhoods and how Istanbulites cross boundaries between them.